Performance of self-curing concrete using baby diapers polymer - Mohamad D.; Beddu S.; Sadon S.N.; Kamal N.L.M.; Itam Z.; Syamsir A.; Mohamad K.; Sapuan W.M. (Research India Publications, 2023)
The advances in construction industry have contributed tremendously for the new developments in construction chemicals. The use of various chemicals in concrete alters the properties of strength and durability. Due to the vast construction activities, different grades of concrete with natural and artificial ingredients are in use. It is observed during construction even though supervision is given importance proper care is not taken in the curing and other operations. As an alternative to water curing, different other methods are also available including membrane curing, polymer curing etc. The water absorbed by the self-curing agent will be gradually released to maximize the heat of hydration and also improve the quality of concrete compare to conventional curing. Therefore, the objective of the research is to determine the effect of waste diapers polymer as a self-curing agent. There are several papers studied on internal curing agent and effect to the concrete. In this research, it will be analyzed by investigating the workability, compressive strength, weight loss and water absorption impact to the concrete. Design Mix with size of cube 100 x 100 x 100mm has been testing day 3, 7, 28 and 90 days with the ratio from 0% as a control and 1%, 2%, 3%, 5% and 10%. From the result that had obtained, 1% of diapers polymers can conclude that the internal curing process can help to improve the hydration process. When the hydration process occurs, the polymer can transfer the water to all part of the concrete and to the hydration point it results the early age cracking can be preventing and promotes maximization of cement hydration, potentially contributing to increase the strength and the fluid transport coefficients can be reduced. Research India Publications.